Does the Impact of Oportunidades Program Increases in Highly Competitive Regions? - Domínguez Viera, Marcos E. (Universidad Autónoma de Nuevo León, 2011)
Evidence on Oportunidades, a successful anti-poverty program in Mexico, has suggested that changes to the current grant structure may induce considerable improvements to its effectiveness. Moreover, there are proposals addressing the importance of regional, observable and unobservable characteristics, regarding its implementation. It is employed competitiveness level outcomes to investigate if this social policy has heterogeneous performance in different regions of intervention. For this purpose, a Difference-in-Difference model is applied to estimate short and mid-term impacts on enrolment rates. Results indicate that the general competitiveness effect is positive but not robust, given the considerable level of aggregation of the data used, whereas if it is distinguised Oportunidades treatment by selected competitiveness outcomes, states with highly efficient government institutions, middle competitive economic sectors and middle inclusive, educated and healthy individuals, present a larger program impact on enrolment rates. It is confirmed the significant improvements to program effectiveness and the impact of the competitiveness JEL Classification: C33, D61, I38, R59.